2020
DOI: 10.1007/s10668-020-01034-z
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in ambient-air-quality reduced temperature during the COVID-19 lockdown period in India

Abstract: The COVID-19 pandemic forced India as a whole to lockdown from 24 March 2020 to 14 April 2020 (first phase), extended to 3 May 2020 (second phase) and further extended to 17 May 2020 (third phase) and 31 May 2020 (fourth phase) with only some limited relaxation in non-hot spot areas. This lockdown has strictly controlled human activities in the entire India. Although this long lockdown has had a serious impact on the social and economic fronts, it has many positive impacts on environment. During this lockdown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…So, it can be said that climate indicators and air quality are not significantly connected with COVID-19 death cases. Several factors are conspiring to bring pollution levels back to levels seen prior to the COVID-19 pandemic, such as calls from some decision-makers and businesses to reschedule Green New Deal projects, reduce vehicle emissions specifications, and stymie the execution of renewable power and inventory work (Pal et al 2021b ). Apart from this, Singh and Chauhan 2020 stated that during the lockdown, air pollution levels decreased significantly, particularly in Delhi and Kolkata, both of which are renowned to be among India’s and the world's most polluted cities.…”
Section: Discussionmentioning
confidence: 99%
“…So, it can be said that climate indicators and air quality are not significantly connected with COVID-19 death cases. Several factors are conspiring to bring pollution levels back to levels seen prior to the COVID-19 pandemic, such as calls from some decision-makers and businesses to reschedule Green New Deal projects, reduce vehicle emissions specifications, and stymie the execution of renewable power and inventory work (Pal et al 2021b ). Apart from this, Singh and Chauhan 2020 stated that during the lockdown, air pollution levels decreased significantly, particularly in Delhi and Kolkata, both of which are renowned to be among India’s and the world's most polluted cities.…”
Section: Discussionmentioning
confidence: 99%
“…The summer temperature for all the cities witnessed a significant decline ( p < 0.05), which can be attributed to lower radiative forcing due to reduced pollutant load in the atmosphere ( Pal et al., 2020 ). The highest difference between the mean summer temperatures was observed in Ghaziabad (1.507).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, correlation analyses between the six air pollutants and the AQI during the three periods were performed to ascertain the sources of air pollutants during and after lockdown. Different studies have already revealed different air quality patterns during active and post-COVID ( Pal, 2021 ; Li, 2021 ). Till August 26, 2021, total doses of COVID-19 vaccination doses administered reach 2 billion and some new cases are still reported in Guangdong, Yunnan, Shanghai, Henan, Tianjin, Liaoning, Heilongjiang, Hubei, and Sichuan in 2021( Baidu, 2021 ).…”
Section: Introductionmentioning
confidence: 99%